The Effect of Electrode Type on The Tensile Strength Characteristics of Welded Joints Between SA.240 Tp.304 Stainless Steel and SA.36 Carbon Steel Alloys through SMAW Welding Process - Azwinur; Syukran; Akhyar; Ferdiyansyah (International Journal of Integrated Engineering, 2022)
Practically, every construction in the industry uses a welding process as a media connecting metal alloys. The quality of the welding joint such as welding strength and defects needs to be maintained especially in dissimilar metals welding process, chemical elements and mechanical properties of the two materials are very much different. The welding strength is influenced by types of joints in welding, butt joints, arc voltages, welding currents, welding speeds, and the electrodes that used. The purpose of this study was to investigate the effect of electrode types on chemical composition, hardness, and tensile strength of dissimilar welded metals between the SA.240 Tp.304 stainless steel and SA.36 carbon steel alloys. Metals welded through a process of gas tungsten arc welding (GTAW) for the root pass, while the filler pass, and capping are welded through a process shielded metal arc welding (SMAW). The electrode used was AWS EWTh-2 or tungsten doped with 2% of tory, the argon gas used 15 lpm with a flow meter volume. Electrode type variations used E309L-16 and E7016 electrodes. Samples of tensile strength cut from two weld joint plates. The tensile test result shows that the electrode type influences the welding strength, this effect by chemical compositions, and the mechanical properties of the core electrode material used. The tensile strength obtained in the welding metal using the E7016 electrode is better than the E309L-16 electrode. The highest tensile strength is 46.83 kgf at the E7016 electrode, while the number of the tensile strength of the E309L-16 electrode is 46.13 kgf.